Design and Analysis of Circular Fractal Array based Micro-strip Patch Antenna for Microwave Applications (International Journal of Current Engineering and Technology, 2015)
In this paper, we presented the design and analysis of micro-strip patch antenna with circular fractals that is suitable for different microwave frequency band applications. A reduction in physical size and multi-band capability are thus important design requirements for antennas in future wireless devices. Two different compact, multi-band circular fractal antenna designs are proposed to operate at different frequency bands in-between 1.0 GHz to 15.0 GHz. The design process consisted of initial theoretical calculations followed by extensive numerical simulations. ANSYS based high frequency structural simulator (HFSS) simulation software were used to design two micro circular fractal array antennas were implemented as micro-strip patches on printed circuit boards (PCB) and were found to perform in agreement with design expectations.
Keywords: Fractal antenna; micro-strip patch; microwave; s-parameter; radiation pattern